Burden of moderate to severe anaemia and severe stunting in children < 3 years in conflict-hit Mount Cameroon: a community based descriptive cross-sectional study - Irene Ule Ngole Sumbele; Gillian Nkeudem Asoba; Rene Ning Teh; Samuel Metuge; Judith Kuoh Anchang-Kimbi; Theresa Nkuo-Akenji (BMC Pediatrics, 2020)
Abstract Background Armed conflict is a significant social determinant of child health with nuanced effects. There is a dearth of knowledge on the public health issues facing vulnerable populations in conflict-stricken areas. The objective was to determine the prevalence and determinants of moderate to severe anaemia (MdSA) and severe stunting (SS) in children ≤3 years in conflict-hit Dibanda, Ekona and Muea in the Mount Cameroon area. Methods Haematological parameters were obtained using an automated haematology analyser while undernutrition indices standard deviation (SD) scores (z- scores), were computed based on the WHO growth reference curves for 649 children in a community based cross-sectional study in 2018. Binomial logistic regression models were used to evaluate the determinants of MdSA and SS against a set of predictor variables. Results Anaemia was prevalent in 84.0% (545) of the children with a majority having microcytic anaemia (59.3%). The prevalence of MdSA was 56.1% (364). Educational level of parents/caregiver (P <  0.001) and site (P = 0.043) had a significant negative effect on the occurrence of MdSA. Stunting, underweight and wasting occurred in 31.3, 13.1 and 6.3% of the children, respectively. Overall, SS was prevalent in 17.1% (111) of the children. The age groups (0.1–1.0 year, P = 0.042 and 1.1–2.0 years, P = 0.008), educational levels (no formal education, P <  0.001 and primary education P = 0.028) and SS (P = 0.035) were significant determinants of MdSA while MdSA (P = 0.035) was the only significant determinant of SS. On the contrary, age group 0.1–1 year (OR = 0.56, P = 0.043) and site (Dibanda, OR = 0.29, P = 0.001) demonstrated a significant protective effect against SS. Conclusions Moderate to severe anaemia, severe stunting and wasting especially in children not breastfed at all are public health challenges in the conflict-hit area. There is a need for targeted intervention to control anaemia as well as increased awareness of exclusive breast feeding in conflict-hit areas to limit the burden of wasting and stunting.